2012
DOI: 10.1111/j.1463-6395.2011.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian maturation and oogenesis in the blue swimmer crab, Portunus pelagicus (Decapoda: Portunidae)

Abstract: Ravi, R., Manisseri, M.K. and K.S., N. 2013. Ovarian maturation and oogenesis in the blue swimmer crab, Portunus pelagicus (Decapoda: Portunidae). -Acta Zoologica (Stockholm) 94: 291-299.The study was aimed at understanding the process of reproduction and the changes happening in the ovary of Portunus pelagicus during maturation, which would be useful for its broodstock development for hatchery purposes. For that, tissue samples from different regions of the ovary at various stages of maturation were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…and Panulirus sp. (Kessel 1968), Coenobita clypeatus (Komm and Hinsch, 1987), Portunus pelagicus (Ravi et al, 2013), and Procambarus fallax f. virginalis (Vogt et al, 2004). However, the presence of coated vesicles in our study both in previtellogenic and vitellogenic oocytes of A. leptodactylus, suggest that before the onset of vitellogenesis, follicle cells can deliver other substance into oocytes by receptor-mediated endocytosis.…”
Section: Ovarian Follicles Compartmentcontrasting
confidence: 63%
See 2 more Smart Citations
“…and Panulirus sp. (Kessel 1968), Coenobita clypeatus (Komm and Hinsch, 1987), Portunus pelagicus (Ravi et al, 2013), and Procambarus fallax f. virginalis (Vogt et al, 2004). However, the presence of coated vesicles in our study both in previtellogenic and vitellogenic oocytes of A. leptodactylus, suggest that before the onset of vitellogenesis, follicle cells can deliver other substance into oocytes by receptor-mediated endocytosis.…”
Section: Ovarian Follicles Compartmentcontrasting
confidence: 63%
“…and Panulirus sp . (Kessel ), Coenobita clypeatus (Komm and Hinsch, ), Portunus pelagicus (Ravi et al, ), and Procambarus fallax f . virginalis (Vogt et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minagawa et al (1993) reported the reproductive biology and the oocyte development in the red frog crab Ranina ranina. The light and electron microscopic details of oogenesis have been carried out in the blue swimmer crab Portunus pelagicus (Ravi et al, 2012). However, there is little information available on oocyte development and vitellogenesis in freshwater crabs (Joshi and Khanna, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Vitellogenesis is the formation of yolk at oocyte in the ovary. Study by Ravi et al, (2013) showed that there were mobilization of FA from hepatopancreas to the ovary at vitellogenesis I and II (from Stage I to Stage III).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%